Psychometric properties of the Norwegian version of the clinical learning environment comparison survey - Camilla Olaussen; Lars‐Petter Jelsness‐Jørgensen; Christine Raaen Tvedt; Dag Hofoss; Ingunn Aase; Simen A. Steindal (Nursing Open, 2021)
Abstract Aim To translate The Clinical Learning Environment Comparison Survey (CLECS) into Norwegian and to evaluate the psychometric properties of the Norwegian version. Design A cross‐sectional survey including a longitudinal component. Methods The CLECS was translated into Norwegian following the World Health Organization guidelines, including forward translation, expert panel, back‐translation, pre‐testing and cognitive interviewing. Nursing students at a Norwegian university college were invited to participate in the study (psychometrical testing) based on informed consent. Reliability and validity of the translated version of CLECS were investigated using a confirmatory factor analysis (CFA), Cronbach's alpha and test–retest analysis. Results A total of 122 nursing students completed the questionnaire and Cronbach alphas for the CLECS subscales ranged from 0.69 to 0.89. CFA goodness‐of‐fit indices (χ2/df = 1.409, CFI = 0.915, RMSEA = 0.058) showed acceptable model fit. Test–retest ICC ranged from 0.55 to 0.75, except for two subscales with values below 0.5